MOIRÉ INTEFEROMETRY APPLIED TO SOIL DYNAMIC STUDIES - MACIEL, ANTONIO JOSÉ DA SILVA; ALBIERO, DANIEL; FABBRO, INÁCIO MARIA DAL (Revista Brasileira de Engenharia de Biossistemas, 2008)
This research work reports the application of a shadow moiré technique as a photoelastic method to support a qualitative stress distribution study on soil samples. The knowledge of stress distribution on undisturbed soil is of unquestionable value to tillage purposes as well as to the civil construction field. The name moiré has its origin in the French language, referring to wave like pattern. When screens of same mesh density are superposed, fringes are generated which move when its relative positions are displaced, it was reported that moiré fringes can be used to magnify displacements, being also suitable as a photoelastic method. The experimental setup for this work included a digital camera to capture the moiré patterns generated for the Ronchi grid and a light source. The images were processed by the softwares named IrfanView, and Idrizi. Five images were taken the sample of clay and they were submitted to varying axial loads kept under the failure stress. Undisturbed samples cylindrical were prepared at the dimensions of 60 mm of height and 60 mm of diameter. Results included the stress distribution maps for each case. It is concluded that the technique get to determine qualitatively the principal stress in soil cylindrical testing specimens.